POINT DEFECTS AND CATION TRACER DIFFUSION IN (TIXFE1-X)3-δO4 1. NON-STOICHIOMETRY AND POINT DEFECTS - Aggarwal S.; Dieckmann R. (My University, 2002)
The deviation from stoichiometry, δ, in spinel solid solutions of the type (TixFe1-x)3-δ O4 with x=0.1, 0.2 and 0.25 was studied thermogravimetrically as a function of oxygen activity, aO2, at 1100, 1200 and 1300 °C. The experimental results, S-shaped curves for δ vs. log aO2, are presented and discussed with regard to the type of point defects prevailing under different conditions in the deviation from stoichiometry. It is concluded that cation vacancies are the predominant point defects at high oxygen activities, while cation interstitials prevail at low oxygen activities. The temperature and composition dependencies of point defect concentrations are also discussed.
Keywords: MAGNETITE; ULVOSPINEL; NONSTOICHIOMETRY; POINT DEFECTS